KOMUNIKASI EKSTRA NORMAL DALAM MEMBANGUN PARIWISATA BUDAYA DI ERA NEW NORMAL - I Putu Agus Aryatnaya Giri; I Made Girinata; I Ketut Wiratmaja (Jurnal Pariwisata Budaya: Jurnal Ilmiah Pariwisata Agama dan Budaya, 2020)
The outbreak of the corona virus in Indonesia, of course, has had a very significant impact in all sectors of life, one of which is in the field of cultural tourism. The closed in and out access between islands, between continents, and between countries has resulted in "vacancies" in tourist destinations, especially in Indonesia. The purpose of this paper is to analyze the way the government communicates to the community in the aspect of cultural tourism in the new normal era using descriptive qualitative research methods. The conclusion of this paper shows that in the midst of the shadow of the positive number of Covid-19 in the new normal era which is still very high, the public's desire to unwind and travel to see the beauty of Indonesian nature and culture can at least be realized by implementing strict rules and Finally, the stretching of the tourism sector community can at least be seen and manifest optimism in other productive sectors. Even so, the challenges seem to come from the society itself, which sometimes does not obey the rules. Because, tourism in the new normal era does require extra normal communication from the government.